Team gymnastics and its impact on the cognitive and motor sphere of students - Butakova E.D. ,; Melnikova T.I. ,; Morozova L.V. ,; Vinogradova O.P. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. The purpose of thisworkis to establishhow the inclusionofteam–building gymnastics elements in the daily routineaffectsthecognitiveandmotorfunctions of students. Methods and structure of the study.In the course of the work, therelationshipbetween the characteristics of teamgymnasticexercisesandfluctuations in biometricindicators of cognitive-motoractivity of 54students(averageage18.5±1.6years)assignedto the mainmedicalgroupforphysical education was studied. The participantsweredividedintoexperimental(n=23)andcontrol(n=21)groups. Results and conclusion. The results of the study confirm the potential benefits of using team-building gymnastics in students' daily lives. The introduction of emotionally intense aerobic exercises performed in a team into the educational process helps restore mental and physical productivity, improves overall well-being and adjusts the optimal mode of psychophysiological activity of students.